Fiestas Patrias Mexican Independence 1995 - Parade and Fiesta - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of the 1995 Fiestas Patrias Parade and Celebration, presented by the San Jose Chapter of the American GI Forum.